(untitled) (Bangladesh Journal of Agricultural Research, 2014)
An investigation was made with a view to estimating inbred and hybrid seed production potentiality as well as fruit yield potentiality of 11 tomato genotypes and their hybrids during November 2009 to September 2010 at Bangladesh Agricultural Research Institute, Gazipur. The highest number of fruits per plant was recorded from the genotype C41 (59.66). The highest fruit yield per plant (2.94 kg) was recorded from the genotype WP8 followed by that of C11 (2.93 kg). In respect of seed yield performance, the genotype C51 produced the highest number of seeds per fruit (47.66), while the line C41 produced the highest seed yield per plant (7.66 g). Per hectare seed yield varied from 263.0 kg (C41) to 53.79 kg (MP5). The highest per plant (6.33 g) and per hectare (139.26 kg) hybrid seeds were produced by the cross combination of C11 X C51 followed by that of WP8 × C11. The fruit weight and fruit yield of the hybrids were much higher compared to their superior parents during the summer season. Among the six tomato hybrids, WP7 X C51 had the highest fruit weight (67.60 g) and produced the highest fruit yield per plant (1.43 kg) followed by BARI Hybrid Tomato-4 (1.24 kg). The other two hybrids, WP8 X C51 (1.08 kg/plant) and C51 X WP10 (1.1 kg/plant) were also found promising. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20057 Bangladesh J. Agril. Res. 39(1): 13-21, March 2014